Selecting medical students: An unresolved challenge*. (March 2015) - Powis, David
Abstract Despite the abundant supply of academically outstanding applicants to medical schools in most countries the regularly recurring debate in the academic literature, and indeed sometimes in the popular media, implies that admissions committees are still getting it wrong in a significant number of instances. How can this be so when our procedures are directed unashamedly at selecting the most highly academically and intellectually qualified students in the expectation that they will make the best doctors? Perhaps it is time for a radical change in emphasis. Instead of endeavouring to differentiate among the top ranks of a pool of outstandingly qualified applicants, the selection effort might be better focused on identifying those potentially unsuitable in terms of their non-academic personal qualities to ensure they do not gain entry. The account that follows is an analysis of the problems of medical student selection and offers a potential solution – a solution that was first suggested in the medical literature 70 years ago, but not adopted. It is the present author's contention that the cycle of debate will continue to recur unless such an approach is pursued.